Laser Protection is Everyone’s Apprehension! An Update - Gopal Krishna Choudhury1, Sangram Panda2, Abhijita Mohapatra3, Gunjan Srivastava3, Abhilash Mohapatr (Institute of Medico-legal Publications Pvt Ltd, 2020)
Today Laser is not anymore limited to big hospitals; it is easily accessible to the private clinics and privateenterprises too. Anyone can go for laser practice today by attending a certified workshop on it. However, themain concern is the sound knowledge of its safety measures and management. This should be the primarygoal for everyone involved in the sale, purchase and practice. There is a mandatory necessity of the safetyadministration or supervision to prevent or safeguard the laser hazards like understanding of standards,recognition of hazards and risks, carrying out of suitable control measures, and unfailing program audit todisplay eminence assurance. Hence, this review topic is taken to update the details of the dental laser hazardsand its management.